Association between various dosage forms of semaglutide and ocular adverse events in a real-world setting - Tao Zhao; Liting Zheng; Yiyun Feng; Min Lao; Yongmei Huang; Guosong Wu (BMC Ophthalmology)
Abstract Background This study systematically compares the risk of long-term ocular adverse events between subcutaneous and oral semaglutide preparations to assess pathway-specific safety differences. Methods In this study, the Report odds ratio (ROR) technique was employed to detect signals of adverse drug reactions (ADRs) associated with the use of semaglutide. Analysis was conducted on data extracted from the FDA Adverse Event Reporting System (FAERS) database, covering the period from 2004(Q1) through 2024(Q3). This investigation encompasses a descriptive analysis focused on the administration of semaglutide through various routes, encompassing a broad range of demographics including gender (male and female), age groups, along with other demographic data and the timing of disease onset. Following this, the study employs the ROR methodology to assess the differential adverse event signals across distinct semaglutide formulations. Results We categorized the eye as the System Organ Class (SOC) and obtained 1733 ADE reports related to it from the FAERS database. Of these, 1541 reports were associated with injectables, while tablets were linked to 192 ADE reports. In both dosage forms, most cases occurred within the first month of administration, although the median time to onset (TTO) differed, with injectables identified at 7.00 [IQR 0.00-56.00] days and tablets at only 3.50 [IQR 0.00-35.00] days. It is worth noting that 5.41% of patients administered subcutaneous injections and 2.17% of those receiving oral medications reported ADEs following one year of treatment with semaglutide. Furthermore, female patients exhibited a higher susceptibility to ocular adverse reactions compared to their male counterparts. Regarding the primary preferred terms (PTs), blurred vision constitutes 34.33% of the total ADEs associated with tablet formulations. This incidence is marginally higher than that observed with injectable formulations. This investigation further discerned ocular ADEs signals associated with specific formulations: subcutaneous injections have a higher frequency of reports concerning retinal complications, such as diabetic retinopathy, ischemic optic neuropathy, retinal detachment, retinal tear, and retinal hemorrhage. Conclusion The results of this study identified a significant difference between subcutaneous and oral semaglutide in ocular ADE risk, providing some evidence for dosage form selection and risk monitoring for clinical use.